Metabolomic analysis of Grifola frondosa mycelium in different culture periods - LIU Jinrong1,2, ZHANG Yancheng2, LIU Yan2, ZHANG Qiang3, LV Huqiang3,4, MOU Guangfu2* (Guangxi Zhiwu)
To gain a comprehensive understanding of the metabolite differences and metabolic pathways involved in the mycelium of Grifola frondosa during various culture periods, this study employed HPLC-MS/MS analysis to thoroughly investigate the mycelium cultured for 10, 20, 30 d. The results were as follows:(1)We identified a total of 584 metabolites belonging to 42 different categories. Notably, among these metabolites, 159, 47, and 165 metabolites exhibited distinct accumulation patterns in the control comparison groups of 10 d vs 20 d, 20 d vs 30 d, and 10 d vs 30 d, respectively. This significant variation in metabolite composition across different culture periods suggested that the metabolic activities of the mycelium were dynamically changing as it grew.(2)During the early stage of culturing(10 d), the mycelium produced a higher concentration of metabolites related to promoting its growth and oxidative energy supply. As the culture progressed to 20 d, the mycelium began to produce or accumulate various secondary metabolites that were beneficial to humans. These included compounds like oleuropein, glycyrrhetic acid, N-methyltyramine, and alprazolam, which were known for their biological activities and potential in health benefits. As the culture progressed to 30 d, the mycelium contained multiple compounds were associated with aroma production.(3)To further understand the underlying metabolic processes, we conducted KEGG metabolic pathway enrichment analysis. This analysis revealed that the comparison groups of 10 d vs 20 d, 20 d vs 30 d, and 10 d vs 30 d were enriched in 163, 81, and 137 metabolic pathways, respectively. Among these, amino acid metabolism emerged as the most significantly influenced pathway in different culture periods, and this finding underscored the importance of amino acid metabolism in driving the metabolic activities of the mycelium during its growth cycle. In conclusion, this study initially explores the differential metabolites and metabolic pathways of the mycelium of G. frondosa, and finds that there are significant differences in the metabolites of the mycelium of G. frondosa in different culture periods, and that the contents of some components in the mycelium is related to the culture time, which has a certain reference value for the quality control and mechanism research of the mycelium of G. frondosa.